2003
DOI: 10.1021/ja038198l
|View full text |Cite
|
Sign up to set email alerts
|

One-Bond, Two-Bond, and Three-Bond Mechanisms in Thermal Deazetizations of 2,3-Diazabicyclo[2.2.2]oct-2-enes, trans-Azomethane, and 2,3-Diazabicyclo[2.2.1]hept-2-ene

Abstract: The thermal deazetizations of a series of substituted 2,3-diazabicyclo[2.2.2]oct-2-enes and some simpler model systems have been studied using the UB3LYP/6-31G(d) and CASPT2 methods, with a variety of active spaces. A fused cyclopropane exerts unique control on the mechanism and rate of deazetization. When the Walsh sigma-orbitals are appropriately aligned in an exo orientation, a pericyclic three-bond cleavage occurs. For an endo-fused cyclopropane, sequential one-bond cleavages occur to take advantage of orb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 29 publications
4
25
0
Order By: Relevance
“…It has been known that the DFT calculation for open shell system is much safer than the MP2 calculation with respect to the spin contamination arising from electronic states with higher multiplicities. [21][22][23] According to the result of recent theoretical study, 8 the UB3LYP and CASPT2 calculations show excellent agreement in predicting the energetics of DBO and DBH systems. Thus, it is clear that the B3LYP (UB3LYP) method with standard 6-311G(d) basis set is good choice to predict the molecular properties for much larger DBH and DBO derivatives with fused rings.…”
Section: Computational Detailsmentioning
confidence: 83%
See 3 more Smart Citations
“…It has been known that the DFT calculation for open shell system is much safer than the MP2 calculation with respect to the spin contamination arising from electronic states with higher multiplicities. [21][22][23] According to the result of recent theoretical study, 8 the UB3LYP and CASPT2 calculations show excellent agreement in predicting the energetics of DBO and DBH systems. Thus, it is clear that the B3LYP (UB3LYP) method with standard 6-311G(d) basis set is good choice to predict the molecular properties for much larger DBH and DBO derivatives with fused rings.…”
Section: Computational Detailsmentioning
confidence: 83%
“…[1][2][3][4] In particular, deazetization (nitrogen loss) of azoalkanes is known to be one of the important routes of formation of photochemically active azo radicals and diradicals. [5][6][7][8] Extensive studies for verifying the mechanisms of such reactions have been reported. [1][2][3][4][5][6][7][8][9][10][11][12][13] The electronic structure of azo chromophores is also believed to play a key role in determining the reaction mechanism and photochemical properties of many azoalkanes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,18,20 This reaction pathway has been predicted to be endothermic when the system reaches the DBH-diyl diradical. At the same time, DBH-diyl has been proposed to be the intermediate species for the formation of the closed-shell bicycle[2.1.0]pentane (BCP-DBH).…”
Section: Resultsmentioning
confidence: 99%